Menejemen Strategi Meningkatkan Motivasi Belajar Siswa di Masa 4.0 - Achmad Qusyairi Mahfudi (Jurnal Manajemen dalam Pendidikan, 2025)
This research aims to explore how teachers implement classroom management in the 4.0 era that is responsive to technological developments, integrates digital tools in daily teaching, and increases student engagement. By utilizing digital platforms, teachers can optimize monitoring of student progress, provide real-time feedback, and facilitate collaboration between students. It is hoped that the results of this research will provide practical guidance for educators in facing the challenges and opportunities that arise in the context of education 4.0 at Darullughah Wal Karomah Middle School. This research uses qualitative methods with a field research approach. Qualitative field research is a research approach that emphasizes in-depth understanding of the natural context of a phenomenon. This method involves collecting data directly from the field, often through participant observation, in-depth interviews, and document analysis. This qualitative research allows researchers to detail social, cultural, and behavioral contexts, as well as explore individual perceptions and interpretations of a phenomenon. The results tend to be descriptive in nature and allow for a deeper understanding of the complexities and nuances in the context under study.